SOME ASPECTS OF LEGAL REGULATION OF AGRICULTURAL PRODUCTS TRADE IN THE EU - G. Martirosyan, Elen (Revista Gênero e Interdisciplinaridade, 2020)
This study deals with certain aspects of the common agricultural policy of the EU and considers some features of legal regulation of agricultural trade in the EU. Legal principles in regulating the organization of agricultural markets are highlighted; the system of intervention price and threshold price is analyzed. It is concluded that the prospects for the development of the agricultural market organization are described by certain economic indicators like production and consumption, exports and imports, acreage, etc. At the same time, there are legal factors that can significantly influence the legal aspects of agricultural trade in the European Union. For example, some of them are the system of mandatory compensation, new environmental standards, etc. A special place is occupied by the result of the reform of the agricultural sector: a system of one-time subsidies for farmers has been introduced.